Growth and mortality of the fish Haemulon aurolineatum (Teleostei: Haemulidae) from Southwest of Margarita Island, Venezuela - Bravo, Edwis (2009)
We analyzed the growth and natural mortality of the fish known locally as cují (H. aurolineatum) in the southwest of Margarita Island, July 2005 to June 2006. A sample of 1 378 males and 1 143 females from artisanal fishing vessels of Boca del Río was analyzed. The common relation for both sexes was expressed by the equation P=0.038*L2.87. The asymptotic length (L∞) was estimated with Powell`s (1979) routine and Wetherall (1986), and the growth coefficient (k) with ELEFAN I - FISAT II (FAO-ICLARM). The modal progression analysis was used after decomposition of lengths frequency according to Bhattacharya, and the estimations of L∞ and k optimized according to Gulland and Holt (1959). The growth curve was fitted to von Bertalanffy (1960); it is exponential, with accelerated growth in the first two years and less growth as the fish approaches maximal length. The rate of natural mortality was high (M=1.15 year-1), and probably was caused by high depredation